Assessment of the effects of Cucumis metuliferus fruits alkaloids against Newcastle disease virus-LaSota - Anne A Anyanwu; Nanloh S Jimam; Noel N Wannang (Wolters Kluwer Medknow Publications, 2016)
Objective: The objective of this study is to investigate the antiviral activity of the Cucumis metuliferus alkaloids against Newcastle disease virus-LaSota (NDV-L). Methods: Hemagglutination (HA) test method using embryonated eggs for study. Results: The result showed "nonlethality" of the alkaloids in 10 days old embryonated eggs. Exposure of the alkaloids to NDV-L infected embryonated eggs showed negative HA test result from varying 2-fold diluted concentration between 50 and 3.125 mg/ml of the alkaloid, while the concentration between 1.563 and 0.195 mg/ml gave positive HA test. Negative HA response means the alkaloids at that concentration have antiviral activities while positive HA test implies the presence of antibodies production in response to an antigen as seen with the control, meaning that viral replication was not inhibited when the embryonated eggs were exposed to lower doses of the alkaloids. Conclusion: The study showed that the alkaloids of C. metuliferus fruit pulp extract have good margin of safety with a high level of antiviral properties as confirmed by the result of the HA test.